Histopathology of `fresh' human aortic valve allografts. Issue 4 (July 1973) - Gavin, J. B.; Barratt-Boyes, B. G.; Hitchcock, G. C.; Herdson, P. B.
Abstract : Gavin, J. B., Barratt-Boyes, B. G., Hitchcock, G. C., and Herdson, P. B. (1973). Thorax, 28, 482-487. Histopathology of `fresh' human aortic valve allografts. Six aortic valve allografts were studied histologically after having functioned in patients as aortic valve replacements for 14 to 442 weeks. The grafts initially had been collected under sterile conditions from cadavers and stored in Hanks's balanced salt solution for 2 to 24 days before use. All grafts showed a cellular reaction along the host graft interface characterized by macrophages, lymphocytes, and organizing granulation tissue, and there was a progressive replacement of the donor aortic sleeve by host collagenous tissue. Sheaths of cellular, avascular host tissue extended from the margins of all grafts over their intimal surfaces and, in those which had been in place more than 36 weeks, this tissue had resulted in thickening of the proximal parts of one or more cusps. In one graft this thickening extended almost to the free margins of the cusps. While the leaflets of the graft at 14 weeks were virtually acellular, older grafts contained cellular areas with active fibroblasts in the proximal regions of the cusps as well as acellular regions which generally were more distally placed. Macrophages were always present along the interface between cellular and acellular areas. These observations indicate that there is a gradual replacement fibrosis of the graft by the host which proceeds in different grafts, and even different cusps in the same graft, at different rates.